Evaluation of the tumor movement and the reproducibility of two different immobilization setups for image-guided stereotactic body radiotherapy of liver tumors - Dreher, Constantin; Oechsner, Markus; Mayinger, Michael; Beierl, Stefanie; Duma, Marciana-Nona; Combs, Stephanie E.; Habermehl, Daniel (Radiation Oncology, 2018)
Background: The purpose of this study is to evaluate the tumor movement and accuracy of patient immobilization in stereotactic body radiotherapy of liver tumors with low pressure foil or abdominal compression. Methods: Fifty-four liver tumors treated with stereotactic body radiotherapy were included in this study. Forty patients were immobilized by a vacuum couch with low pressure foil, 14 patients by abdominal compression. We evaluated the ratio of gross tumor volume/internal target volume, the tumor movement in 4D-computed tomography scans and daily online adjustments after cone beam computed tomography scans. Results: The ratio of gross tumor volume/internal target volume was smaller with low pressure foil. The tumor movement in 4D-computed tomography scans was smaller with abdominal compression, the cranial movement even significantly different (p = 0.02). The mean online adjustments and their mean absolute values in the vertical, lateral and longitudinal axis were smaller with abdominal compression. The online adjustments were significantly different (p < 0.013), their absolute values in case of the longitudinal axis (p = 0.043). There was no significant difference of the adjustments' 3D vectors. Conclusions: In comparison to low pressure foil, abdominal compression leads to a reduction of the tumor movement. Online adjustments decreased significantly, thus leading to higher accuracy in patient positioning.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Liver tumor; Patient immobilization; Robustness; Stereotactic body radiotherapy